KEBIJAKAN SISTEM RECRUITMENT DAN PELATIHAN KARYAWAN PADA TURNOVER RUMAH MAKAN COBEK SOLOYONG - Icha Nurfadilah Anwar; Puput Hermaliana Puput; Santi Pertiwi; Dwi Epty Hidayaty (PT Naureen Digital Education, 2023)
This study aims to determine employee recruitment and employee training that lead to turnover in UMKM Cobek Soloyong H.Maman Restaurant. And also to find out how recruitment and training should be applied to UMKM Cobek Soloyong H.Maman Restaurant. This research was conducted by means of descriptive observation and interviews with the owners and employees of the Cobek Soloyong Restaurant. The recruitment policy implemented in UMKM is that recruitment still uses a family system. And also low employee training, especially in changing or moving employees so that turnover occurs. Employee recruitment and training that should be carried out is recruitment in accordance with company procedures in general, namely by determining criteria such as age, expertise, experience, and education. And employee training is carried out by carrying out several tests, namely, ability tests, demonstration tests, personality tests, and field practice tests directed by the owner of the restaurant. The results of this study are that the influence of Employee Recruitment and Training Policies on the Turnover of the Cobek Soloyong H. Maman Restaurant has a positive but not significant effect. Keywords: Policy; Recruitment; Training.